ANALISIS MENAJEMEN KESELAMATAN PASIEN TERHADAP MUTU PELAYANAN KESEHATAN DI RUANG RAWAT INAP RUMAH SAKIT X - Azzahra, Siti Khumairah; Girsang, Ermi; Nasution, Sri Wahyuni (Poltekkes Kemenkes Bandung, 2022)
The most significant metric in the health care system is patient safety, which is meant to serve as a guide in providing the best possible care and lowering patient occurrences. The study's objective is to examine the impact of patient safety management on the standard of care provided in the inpatient unit at X Hospital. Qualitative research methodology is used. The patient safety team, the nursing committee, and the head of quality improvement and patient safety made up the five informants for the September 2022 study. Through observations and interviews, data was gathered. Collaizzi is used in data analysis to reduce data, show data, and draw conclusions.The research results show that there are five themes, namely that the role of the organization in determining patient safety management has been supported by mentors and experts. This is shown by the results of interviews, namely that there are mandatory, meetings, in-house training, reviews and also adequate human resources. Ensuring that patient safety management is supported by mentors and experts, this is shown by the results of interviews, namely that there are mandatory requirements, meetings, in-house training, reviews and also adequate human resources. It is recommended that hospital management provide training and socialization about patient safety programs on a regular basis, provide sanctions for violating the implementation of Standard Operating Procedures and propose a report form using an online system.